(3GdeSFhdjI GdeOfjI ddeMGei JLGg GdYejd (B/s - (3eMeO YHOGdXGgQ MSjf s; (3MeOj YHOGdQMefs; (3fRjg eMeO GdUGOb GdegOjs; (3Ydj MSjf fLjOgs ([(3GdbGgQI(B] : s (3eMeO YHOGdXGgQ MSjf , s, 1990)
(3JfGhd GdHMK OQGSI GdYdGbI GdYbOjI Hjf GdWQajf (B((3GdeMGei, GdYejd(B) (3hfhbT GdQCi GdfGXQ Edi gPg GdYdGbI Ydi CfgG dGJchf YbOG eOfjG edReG eQJCjG ai GdeMGei Cfg jDOi NOeI YGeI JJYdb HeQab YGe GdG hgh eQab GdYOGdI(B. (3ceG fGbT GdJcjjaGJ GdeNJdaI ddYbO Hjf GdeMGei hGdYejd hYQV ddJcjja GdPi CNPJ Hg CZdHjI Gdabg hfGUQg GdEJLGg GdZGdH ai GdbVGA MjK jQi ai GdYdGbI Hjf GdeMGei hGdYejd YbO hcGdI(B. (3Ke JMOK Yf GdJRGeGJ GdYejd JLGg eMGejI hGdJi JXgQ ai UhQI GdCJYGH GdeSJMbI ddCNjQ(B. (3ceG JfGhd LRGA GNdGd GdeMGei HeG Ydjg ef GdJRGeGJ hYQV dCSGS GdeSFhdjI, Ke YQV dWHjYI GdJRGe GdeMGei JLGI YejdI ef NdGd YQV GdfXQjI GdJbdjOjI GdNGUI HJbSje GdCdJRGeGJ Edi GdJRGe HfJjLI hGdJRGe HhSjdI, Ke fGbT YfGUQ eSFhdjI GdeMGei GdeOfjI ef NdGd YQV ddYfGUQ GdeYQhaI ai GdbGfhf GdeOfi hgi GdJbUjQ ai COGA GdCdJRGe hGdVQQ GdfGJL Yfg Ke YdGbI GdSHHjI HjfgeG, ceG YQV CjVG dcjajI JbOjQ GdJYhjV Yf VjGY GdaQUI aEPG cGf GdEJaGb bO bGe Ydi EYJHGQ GdaQUI GdVGFYI ai MO PGJgG VQQG eMbbG jfHZi JYhjV GdYejd Yfgs
(3GWQhMI OcJhQGgs
(3JTJed Ydi EQLGYGJ HHdjhLQGajI s
Keywords: (3GdeSFhdjI GdeOfjIs -- (3GdeMGehfs